The role of nurses in the application of bedsores in palliative care - Andriulevičienė, Lina (Slauga. Mokslas ir praktika, 2022)
In palliative care, the role of the nurse is very important in the prevention of bedsores, as only by providing qualified care and early prevention can bedsores be prevented and thus improve the patient's quality of life in the last years of life. The role of nurses in the prevention of bedsores is mainly reflected in the use of bedding prevention and treatment mattresses and functional beds. Less than three-quarters of nurses often use biophysical agents, various bandages, auxiliary surfaces, heel guards, stationary lifts, flip-flops, transfer boards / stretchers / belts, and other positioning devices in palliative care. According to the recommendations of the EPUAP, almost half of nurses say that the most effective means of preventing bedsores in palliative care is flipping. Nurses perform many professional and effective actions, functions that improve the patient's health and well-being in the treatment of bedsores. Also, in the prevention of patients' bedsores and palliative care, nurses perform their work responsibly, reliably, and are able to empathize with patients.The aim. To elucidate the role of nurses in the application of bedsores in palliative care.Research methods: after analyzing the scientific literature, from 2021. A quantitative survey and an anonymous survey were conducted in November-December. The research data were analyzed by MS Office Excel 2016 data processing program. The research was conducted in accordance with ethical principles.Results of the study: 64 nurses (women) participated in the study. The productive role of nurse in the prevention of bedsores is reflected in the use of EPUAP guidelines in the prevention of patient bedsores.Conclusions: The study found that 94 percent. (n = 60) the role of nurses in the prevention of bedsores is reflected in the most common use of bedsores for the prevention and treatment of bedsores, 91%. (n = 58) - uses functional beds. On average, 67 percent. (n = 43) nurses often use biophysical agents, various bandages, auxiliary surfaces, heel guards, stationary lifts, flip-flops, transfer boards / boards / stretchers / belts and other positioning devices, with the least use of implants - 39%. (n = 25). According to the EPUAP, 46 percent. (n = 29) The most effective measures for nurses in the prevention of bedsores in palliative care are reversal, and 17%. (n = 11) - when more employees work, 11 percent. (n = 7) - patient hygiene and dry maintenance, 8 percent. (n = 5) - bed rest mattresses and functional beds.
Keywords: role of nurse; bedsores; bedsores prevention; palliative care